Mechanistic exploration of Traditional Chinese Medicine regulation on tumor immune microenvironment in the treatment of triple-negative breast cancer: based on CiteSpace and bioinformatics analysis - Feng, Dandan; Pu, Dongqing; Ren, Jinlu; Liu, Ming; Sun, Xiaohui; Zhang, Zhen; Li, Jingwei (Frontiers in Immunology, 2025)
BackgroundTriple-negative breast cancer (TNBC) is a highly aggressive subtype of breast cancer, characterized by frequent recurrence, metastasis, and poor survival outcomes despite chemotherapy-based treatments. This study aims to investigate the mechanisms by which Traditional Chinese Medicine (TCM) modulates the tumor immune microenvironment in TNBC, utilizing CiteSpace and bioinformatics analysis.MethodsWe employed CiteSpace to analyze treatment hotspots and key TCM formulations, followed by bioinformatics analysis to identify the main active components, targets, associated pathways, and their clinical implications in TNBC treatment.ResultsCiteSpace analysis highlighted key TCM formulations, including Sanhuang Decoction. Network pharmacology identified major bioactive components such as Mutatochrome, Physcion diglucoside, Procyanidin B-5,3’-O-gallate, gallic acid-3-O-(6’-O-galloyl)-glucoside, and isomucronulatol-7,2’-di-O-glucosiole, with core targets including Mitogen-Activated Protein Kinase 1 (MAPK1), Janus Kinase 2 (JAK2), and Lymphocyte-specific protein tyrosine kinase (LCK). These targets were found to be involved in immune regulation, particularly the modulation of CD8+ and CD4+ T cells. Additionally, core targets were associated with improved recurrence-free survival (RFS) and overall survival (OS) in TNBC patients.ConclusionThe therapeutic effects of TCM in TNBC primarily involve immune modulation within the tumor microenvironment, particularly through the regulation of CD8+ and CD4+ T cells.